The Correlation Between Thyroid Function, Frontal Gray Matter, and Executive Function in Patients With Major Depressive Disorder - Zhao, Shuai; Xia, Yi; Huang, Yinghong; Zou, Haowen; Wang, Xumiao; Chen, Zhilu; Zhou, Hongliang; Han, Yinglin; Tang, Hao; Yan, Rui; Yao, Zhijian; Lu, Qing (Frontiers in Endocrinology, 2021)
The present study was aimed to investigate the relationships between serum thyroid hormones (THs), frontal gray matter volume, and executive function in selected patients with major depressive disorder (MDD). One hundred and four MDD patients and seventy-five healthy controls (HCs) were subjected to thyroid-stimulating hormone (TSH), free Triiodothyronine (fT3), free Thyroxine (fT4), and executive function tests and underwent structural magnetic resonance imaging (MRI). Voxel-based morphometry (VBM) analysis was performed to compare group differences in the gray matter for the frontal lobe. Furthermore, mediation analysis was used to investigate whether gray matter volumes of the frontal gyrus mediated the relationship between serum THs and executive function in MDD patients. MDD patients exhibited significant gray matter volume reduction in several brain regions, including the left rectus, right middle frontal cortex, and left middle frontal cortex. Serum TSH levels are positively associated with altered regional gray matter volume patterns within MFG and executive function. Importantly, gray matter in the right MFG was a significant mediator between serum TSH levels and executive function. These findings expand our understanding of how thyroid function affects brain structure changes and executive function in MDD patients.